KINERJA LUMBUNG PANGAN DALAM MENDUKUNG KETERSEDIAAN PANGAN RUMAH TANGGA DI KABUPATEN PRINGSEWU - Mahmud Rifa’i; Fembriarti Erry Prasmatiwi; Indah Nurmayasari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This research aims to analyze the mechanism of food granary in supporting household food availability, performance of food granary institution, and factors that affect the performance of the food granary in Ambarawa Subdistrict Pringsewu Regency.  The location was determined purposively with consideration that Ambarawa Subdistrict is one district which has a lot of active food granary institutions.  Data were collected in September 2016.  The samples were determined proportionately randomly, as many as 30 active food granaries in Ambarawa village, Ambarawa Barat village, and Sumber Agung village.  This research used a survey method, and the data were analyzed using qualitative and quantitative descriptive analysis.  The results showed that the mechanism of food granary was realized by saving and borrowing of unhusk rice.  The members of food granary can borrow as much as 100 – 1,000 kilograms of rice per year.  They borrow rice at the time of scarcity before harvest time, and save rice after harvest time.  The results showed that the performance of 46.67 percent of food granaries are categorized in a low level and 53.33 percent in medium level.  Factors that affect the performance of food granary in Ambarawa Subdistrict, Pringsewu Regency, are the age of food granary, the number of members, and the kind of food granary. Key words: food availability, food granary, performance